The effectiveness of interventions in workplace health promotion as to maintain the working capacity of health care personal - Buchberger, Barbara (German Medical Science GMS Publishing House, 2011)
BACKGROUND: The increasing proportion of elderly people with respective care requirements and within the total population stands against aging personnel and staff reduction in the field of health care where employees are exposed to high load factors. Health promotion interventions may be a possibility to improve work situations and behavior. METHODS: A systematic literature search is conducted in 32 databases limited to English and German publications since 1990. Moreover, internet-searches are performed and the reference lists of identified articles are scanned. The selection of literature was done by two reviewers independently according to inclusion and exclusion criteria. Data extraction and tables of evidence are verified by a second expert just like the assessment of risk of bias by means of the Cochrane Collaboration’s tool. RESULTS: We identified eleven intervention studies and two systematic reviews. There were three randomized controlled trials (RCT) and one controlled trial without randomization (CCT) on the improvement of physical health, four RCT and two CCT on the improvement of psychological health and one RCT on both. Study duration ranged from four weeks to two years and the number of participants included from 20 to 345, with a median of 56. Interventions and populations were predominantly heterogeneous. In three studies intervention for the improvement of physical health resulted in less complaints and increased strength and flexibility with statistically significant differences between groups. Regarding psychological health interventions lead to significantly decreased intake of analgesics, better stress management, coping with workload, communication skills and advanced training. DISCUSSION: Taking into consideration the small to very small sample sizes, other methodological flaws like a high potential of bias and poor quality of reporting the validity of the results has to be considered as limited. Due to the heterogeneity of health interventions, study populations with differing job specializations and different lengths of study durations and follow-up periods, the comparison of results would not make sense. CONCLUSIONS: Further research is necessary with larger sample sizes, with a sufficient study duration and follow-up, with a lower risk of bias, by considering of relevant quality criteria and with better reporting in publications.